METODE EKSPERIMEN DALAM KEGIATAN EKSTRAKURIKULER MUSIK DI SMAN 7 PADANG - Deby Cloveando Mondely; Syeilendra Syeilendra; Harisnal Hadi (FBS Universitas Negeri Padang, 2018)
AbstractExtracurricular activities are often called ekskul is an extra activity within the institution, which is carried out outside the intrakurikuler activities. Extracurricular activities are intended so that students can develop a keen interest, talents and creativity in various academic fields outside. Own means extracurricular activities conducted outside of the students learn the curriculum standards. These activities exist at every level of education ranging from primary school up to College. This study aims to describe the process of the implementation of the experimental Method in the activities of extracurricular music in SMAN 7 field. In the learning activities of the teacher plays an important role in the achievement of learning objectives. An understanding of the implementation and mastery of the material by the teacher will become a reference in order to achieved the goal of learning. This type of research is a method of experimentation. The main instrument in this study is the researchers themselves. The tools used in this research is a form of writing instruments and cameras. the research of using primary data and secondary data, while the data collection technique through the study of librarianship, observation, interviews, and documentation. The research results showed that extracurricular activities in high school music N 7 the field gets a high from appreciative students, as well as many of the students who are interested in following the activities of the ekstrakurikule music halini aims so that students can improve creativity in playing music. In extracurricular activities students can add insight and knowledge of music.Key Words : Media, Audio visual, Learning